Family Christmas at Frances Kamp's San Mateo Home - Watkins, Howard::::::::: (1984)
Frances Kamp, Gail Graham, Adam Watkins, Christine Watkins, Greg Graham squatting, Jackie Hijmans, Cary Hijmans, Greg Graham, ?, Jerry Kamp in front yard